Engineering for desiccation postponement: antisense of sucrose transporter in tobacco specifically on guard cells results in reduced stomatal conductance and increased water use efficiency - Antunes, Werner Camargos (2009)
It was evaluated the importance of guard cell (GC) sucrose transporter and the role of sucrose as osmotic on GC. We transformed tobacco plants with antisense gene construct for sucrose transporter driven by KST1, GC specific promoter. Transgenic plants GC have less sucrose, more starch and modest increase in K + contents. Low sucrose contents in GC of transgenic lines were associated with low stomatal conductance (g s ), suggesting the importance of sucrose transporter and symplastic sucrose in maintaining low osmotic potential on GC. It was observed rapid starch disappearance when the guard cells are swelling, fact not observed in control plants. By means of low g s tobacco plants demonstrated diffusional (stomatal) restriction of photosynthesis (A), low transpiration rate (E) and low sub-stomatal CO 2 concentration, high A/E and higher carbon rate composition (δ 13 C). However, higher A/E was associated with lower A, consequently, a slower crop growth rate, but not smaller “efficiency index” as showed by relative growth rate. The δ 13 C data confirms the low conductance, showing that it represents a common stomata behavior over all plant development. By means of low g s tobacco plants, we got desiccation postponement phenotype as principal feature of this transformation, being high water saving plants. These results suggest that manipulation of sucrose transport in GC may be developed as a practical mechanism for drought avoidance and water conservation during irrigation. These results illustrate the importance of fine tuning of sucrose metabolism transport and metabolism in the fitness of stomatal function in contributing to plant survival or growth under unfavorable water conditions.